Timeliness of Human Immunodeficiency Virus Diagnosis and Antiretroviral Treatment Initiation in the Era of Universal Testing and Treatment. (4th April 2019) - Robertson, McKaylee M; Braunstein, Sarah L; Hoover, Donald R; Li, Sheng; Nash, Denis
Abstract: Background: We describe the timing of human immunodeficiency virus (HIV) diagnosis and antiretroviral treatment (ART) initiation after implementation of universal testing and treatment policies in New York City (NYC). Methods: Using NYC population-based HIV registry data for persons with HIV diagnosed from 2012 through 2015 and followed up through June 2017, we examined trends in the proportion with diagnosis soon after HIV infection (ie, with CD4 cell count ≥500/μL or with acute HIV infection) and used Kaplan-Meier plots and proportional hazards regression to examine the timing of ART initiation after diagnosis. Results: Among 9987 NYC residents with HIV diagnosed from 2012 to 2015, diagnosis was early in 35%, and 87% started ART by June 2017. The annual proportion of persons with early diagnosis did not increase appreciably (35% in 2012 vs 37% in 2015; P = .08). By 6 months after diagnosis, 62%, 67%, 72% and 77% of persons with HIV diagnosed in 2012, 2013, 2014, or 2015, respectively, had started ART, with median (interquartile range) times to ART initiation of 3.34 (1.34–12.75), 2.62 (1.28–10.13), 2.16 (1.15–7.11), and 2.03 (1.11–5.61) months, respectively. Conclusions: Although recommendations for ART initiation on diagnosis are increasingly being implemented, the findings of the current study suggest that immediate treatment initiation is not universal. Continued efforts are needed to expand and better target HIV testing to promote earlier diagnosis. Abstract : We observed a slow but steady trend toward earlier ART initiation after universal treatment guidelines were implemented in 2012, suggesting that local and national recommendations for ART initiation on diagnosis are increasingly being implemented in New York City.